Assessment of Nutrient Availability and Microbial Soil Biomass under Different Level of Potassium Humate and Fertility in Mungbean (Vigna radiata) - Kumar, Yogesh; Verma, Rajhans; Singh, Kuldeep; Aakash; Bhukhar, Oma Shanker (International Journal of Economic Plants, 2022)
A field trial was conducted to study soil quality parameters influenced by different levels of potassium humate and fertility under mungbean cultivation at SKNAU, Jobner during kharif season of 2019. The experiment was carried out in a factorial randomized block design with three replications and sixteen treatment combinations. Along with nutrients status in the soil after harvest, soil microbial properties were assessed. The response of potassium humate and fertility levels on nutrient content and soil microbial properties were found to be significant. Application of potassium humate @ 4.5 kg ha-1 was recorded maximum OC (%), N, P2O5, K2O (kg ha-1), S, DTPA-Zn and Fe (mg kg-1) (0.23, 158.22, 22.00, 178.00, 9.61, 4.21 and 0.64, respectively) followed by potassium humate @ 3 kg ha-1 over control. Among different fertility levels, 100% RDF recorded a significantly higher value of above available nutrients in soil over control but DTPA-Zn, Fe, S and OC% did not significantly affect by different fertility levels. Application of potassium humate @ 4.5 kg ha-1 and 100% RDF was recorded improved soil microbial biomass viz., microbial biomass C, N, P, dehydrogenase enzyme and alkaline phosphatase activity over control.